1995
DOI: 10.1103/physrevlett.74.1450
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Peierls State versus Néel State in Doped CuGeO3

Abstract: Spin-Peierls state versus Néel state in doped CuGeO3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
112
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(124 citation statements)
references
References 26 publications
11
112
0
1
Order By: Relevance
“…Investigations have concentrated on systems where Cu atoms were replaced with Zn [14][15][16][17][18][19] or Ge was replaced with Si. [20][21][22] It is now well established that a new antiferromagnetic (AF) ordered phase appears at low temperatures in both Zn-doped 14,19 and Si-doped 22 samples.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations have concentrated on systems where Cu atoms were replaced with Zn [14][15][16][17][18][19] or Ge was replaced with Si. [20][21][22] It is now well established that a new antiferromagnetic (AF) ordered phase appears at low temperatures in both Zn-doped 14,19 and Si-doped 22 samples.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, it has been shown that the contributions to the susceptibility from doping-induced impurity spins in spin-Peierls systems at low temperatures deviate heavily from the Curie-law behaviour one would expect for purely exponentially decaying correlation functions 15,21 . Other examples are the transition to an ordered antiferromagnetic phase, the Néel phase, occuring at unexpectedly high temperatures [21][22][23][24] , and the temperature dependence of the specific heat in these materials 21 .…”
mentioning
confidence: 99%
“…For specific compounds and doping conditions, certain predictions of the model, such as phase transitions or long-range ordering, have been experimentally tested, either by the measurement of macroscopic quantities 22,24,25 or by scattering techniques 23,[26][27][28] . However, some configurations are difficult to investigate experimentally, such as the impact of boundaries 29 or spatial variations in the coupling or dimerization strength.…”
mentioning
confidence: 99%
“…The SP transition is evidenced by a kink at T SP in the magnetic susceptibility and is clearly revealed by X-ray and neutron scattering 2 . A unique feature of this compound is that the effect of impurities can be studied by substituting impurity ions (Zn, Mg and Ni) for the Cu sites [3][4][5][6][7][8] and Si for the Ge sites 9 . These substitutions all induce a strong decrease of T SP and the appearance at lower temperature (T < T N < T SP ) of a three-dimensional AF phase.…”
Section: Introductionmentioning
confidence: 99%